The impact of strategic analysis of operating income on managerial decision-making A case : study in (Kawa) carpentry factory in Erbil Governorate for the manufacture of wooden counters for kitchens - abdullah jaf, rizgar; nawzad ahmed, Safaa; ibrahim omer, Banaz (Iraqi Journal for Administrative Sciences, 2024)
The research aims to develop an integrated mechanism and practical steps on how to apply strategic analysis of operating income to arrive at the laboratory's ability to rely on the results of the analysis to make administrative decisions (strategic, operational and organizational) and to calculate the elements of strategic analysis in a more accurate manner. The process of calculating the deviations and distributing them on the basis of strategic analysis has been relied on (growth component, price recovery component and productivity component in Kawa Carpentry Factory in Erbil Governorate for the manufacture of wooden counters for kitchens based on the existing information The operating income obtained from the laboratory records The research sample for two years (2018-2019). The research concluded the importance of applying the research sample strategic analysis of operating income in calculating the deviations of the income statement for the years (2018-2019) and classifying them on the elements of growth, price recovery and productivity, taking into consideration the results of the analysis as a basis for evaluating and implementing the strategic performance in the laboratory and for identifying strengths and weaknesses and taking the necessary administrative decisions that enable The lab to continue and go towards better performance.